2019
DOI: 10.1101/523563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D spatial organization and network-guided comparison of mutation profiles in Glioblastoma reveals similarities across patients

Abstract: Mutation profiles of Glioblastoma (GBM) tumors are very heterogeneous which is the main challenge in the interpretation of the effects of mutations in disease. Additionally, the impact of the mutations is not uniform across the proteins and protein-protein interactions. The pathway level representation of the mutations is very limited. In this work, we approach these challenges through a systems level perspective in which we analyze how the mutations in GBM tumors are distributed in protein structures/interfac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We previously demonstrated that stratification of mutations observed in glioblastoma multiforme tumors as 3D patches reduces interpatient heterogeneity and provides distinct druggable 3D mutation signatures (Dincer et al, 2019). Grouping phosphorylation sites based on their 3D position would provide distinct functional signatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that stratification of mutations observed in glioblastoma multiforme tumors as 3D patches reduces interpatient heterogeneity and provides distinct druggable 3D mutation signatures (Dincer et al, 2019). Grouping phosphorylation sites based on their 3D position would provide distinct functional signatures.…”
Section: Discussionmentioning
confidence: 99%
“…The more negative score represents the more damaging mutation. Dincer et al (Dincer et al, 2019) have previously shown that mutations in the interface and core regions have more damaging effects than on the surface. In line with that, the same applies to phospho-sites as well.…”
Section: Structural Stratification Of Human Phosphorylation Sites Reveals Their Signature Propertiesmentioning
confidence: 99%
“…Curated driver genes and mutations have been deposited in multiple databases [8][9][10]and used by multiple research groups to develop computational approaches to predict driver genes and driver mutations [11][12][13][14][15][16]. These methods, including the frequency-based methods, subnetwork identification methods, and 3D mutation search methods, have been comprehensively compared [17][18][19]. One of the concerns with frequency-based approaches is that prohibitively large sample sizes are needed to identify infrequently mutated driver genes.…”
Section: Introductionmentioning
confidence: 99%